Improving dual cover crop mixtures to increase shoot biomass production and weed suppression potential - Groß, Jonas; Kümmerer, Robin; Heuermann, Diana; Gentsch, Norman; Schweneker, Dörte; Feuerstein, Ulf; Guggenberger, Georg; von Wirén, Nicolaus; Bauer, Bernhard (Frontiers in Agronomy, 2024)
IntroductionCover crop services depend on biomass production and species composition of the cover crop stand. In this study, we investigated the interactions in shoot biomass of dual cover crop mixtures and their competitiveness to suppress weeds before winter under different growing conditions.MethodsA field experiment was performed on sandy loam soil in Triesdorf, Germany, for two consecutive years. The cover crop species white mustard (Sinapis alba L.), oil radish (Raphanus sativus var. oleiformis L.), phacelia (Phacelia tanacetifolia J.), Egyptian clover (Trifolium alexandrinum L.), common vetch (Vicia sativa L.), field pea (Pisum sativum L.), and field bean (Vicia faba L.) were grown in pure stands or dual mixtures. Cover crops were sown in August, and shoot biomass was harvested at the end of the vegetation period. Cover crop shoot biomass was dried, and the share of each species and the sown test weed (Brassica napus L.) were determined.ResultsThe share of shoot biomass of a cover crop species in dual-species mixtures was closely related to its shoot biomass in its pure stand. In both years, mustard and phacelia showed similar interactions in shoot biomass production when growing with a second species. Regarding competitiveness against weeds, cruciferous species outperformed other cover crop species and could suppress weeds even if they were mixed with a less competitive partner. Weed suppression of mixtures with phacelia depended on the second component in the mixture and was more effective in a dry season. Legume species, especially Egyptian clover and common vetch could not suppress weeds in a pure stand.DiscussionOur results show that species with high weed suppression potential as single stands retain this ability in dual cover crop mixtures, regardless of the suppression potential of the second species that completes the mixture.